EFL Students’ Achievement and Affective Factors on Reading Comprehension: A Literature Study - Gumartifa, Asti (LPPM Universitas Pancasakti Tegal, 2021)
Reading is an interactive activity in which readers use successful reading strategies to create a meaningful representation of a text. The purpose of this study was to describe the effects of achievement and affective factors on reading comprehension. The research's goal is to review the national and international literature on reading skills and reading comprehension achievement. The researcher explained the terms reading and reading comprehension as well as the principles for teaching reading. Problems, competencies, techniques, and types of reading comprehension were also discussed. According to a review of the research, teachers and students require wide information specifically in terms of reading comprehension to acquire reading comprehension effectively.